Significações constituídas por professoras e alunos do ensino fundamental sobre o racismo na escola - Oliveira, Priscila da Silva (2019)
Racism is a social phenomenon that consists of prejudice and discrimination based on ethnic differences between peoples. The African-Brazilian still suffers from the inheritance of the slave-owning period, in which, for centuries, Africans and their descendants were condemned to slavery, preventing them from having the same conditions of humanization as European whites. The present research aims to analyze the meanings of racism made by teachers and students in a school located in the north of the city of São Paulo. For this study, semi-structured interviews were conducted with four self-declared white and black female teachers and four self-declared white and black students. The study was based on the literature of authors such as Gomes (2002), Munanga (2004), Bento (2009), Rosemberg (2014) and Ronca (2016), anchored in the methodological assumption of Sociohistorical Psychology, based on Dialectical and Historical Materialism. During the interviews, teachers and students discuss the meaning-making process on the phenomenon of racism in the school environment, how it is perceived in the classroom, what kind of visibility is given to racial issues in the school and what interventions are carried out against racist practices that occur in everyday school life. The analysis was carried out through indicators and pre-indicators structured to form the nucleus of meanings, as proposed by Aguiar and Ozella (2016). From the narratives, it is possible to state that racism is expressed in the school space explicitly by means of cursing and discriminatory jokes, veiled, naturalized or confused and reduced to bullying. Although the school is considered a center of reference for African culture and has a specific project for the promotion of racial equality, there is no reflection whatsoever on how to treat children who suffer from racism in the school environment. The importance that white teachers and students give to the subject has also been addressed, as well as law 10.639 / 03, which reinforces the teaching of African and African-Brazilian cultures in school. A partnership between school management and teachers to combat racism is also discussed